Theoretical Energy and Exergy Analyses of Proton Exchange Membrane Fuel Cell by Computer Simulation. (18th September 2016) - Gimba, I. D.; Abdulkareem, A. S.; Jimoh, A.; Afolabi, A. S.
Abstract : A mathematical model of a proton exchange membrane fuel cell (PEMFC) was developed to investigate the effects of operating parameters such as temperature, anode and cathode pressures, reactants flow rates, membrane thickness, and humidity on the performance of the modelled fuel cell. The developed model consisted of electrochemical, heat energy and exergy components which were later simulated using a computer programme. The simulated model for the voltage output of the cell showed good conformity to the experimental results sourced from the literature and revealed that the operating pressure, temperature, and flow rate of the reactants positively affect the performance and efficiencies (energy and exergy) of the cell. The results also indicated that high membrane thickness above 150 μ m is unfavourable to both the fuel cell performance and the cell energy and exergy efficiencies. The simulated results obtained on the influence of membrane humidity on the cell performance indicated that membrane humidity positively favours both the performance and energy and exergy efficiencies of the cell. It can therefore be inferred that the performance of the PEMFC and energy and exergy efficiencies of the cell are greatly influenced by the operating pressure, temperature, membrane thickness, membrane humidity, and the flow rates of fuel and oxidant.